Imperfection of Entropy Principles in the Implementation of Supply Chain Strategy Measures to Promote Goods in the Media - D Volkov; V Vishnyakova; A Shatsky (International Journal of Supply Chain Management, 2019)
The system of relations between the consumer and the seller has many factors that shape the dynamics of the market of goods and services based on the supply chain strategy. Supply chains satisfy customers by striving for delivering the right products to the right place at the right time, at the right quality and at the right quantity within an increasingly faster pace and lower cost. Theories of social entropy consider the system of social relations from the standpoint of the equilibrium of systems and their disproportion. The equilibrium state of the market of goods and services is possible only in theory. Market failures in every way prevent the emergence of an equilibrium state. Promotion of goods in modern conditions is considered the norm. However, advertising is increasingly faced with negative reviews of consumers of goods and services in the media space. A large number of advertising destroys this system, on the one hand, and on the other, transforms the sphere of information content in the media.